Sources and Radiative Impact of Carbonaceous Aerosols Using Four Years Ground-Based Measurements over the Central Himalayas - Priyanka Srivastava; Manish Naja; T. R. Seshadri (Aerosol and Air Quality Research)
Abstract Climate and health in the pristine Himalayan region are largely impacted by the transport of carbonaceous aerosols from the polluted regions of Asia and Europe. Yet, there is a scarcity of source apportionment studies that can explain diurnal scale phenomena concerning various emission sources and radiative forcing. Here, we report the first simultaneous high-resolution delineation of primary organic carbon (POC) and secondary organic carbon (SOC) content and quantify the contributions of fossil fuel combustion and biomass burning over the Central Himalayas using four-year (2014–2017) online observations. Four different methods are employed to deconvolute organic carbon (OC) into POC and SOC. Unlike SOC, POC exhibits significant unimodal diurnal variations with higher values during daytime in all four methods. These methods show intra-annual variations in POC (56–80%) and SOC (20–44%) concentrations but they agree that overall POC (4.7–8 µg m−3) dominates over SOC (2.4–3.9 µg m−3). The role of crop residue burning in northern India and forest fires is shown to be dominant in spring while local heating-purpose emissions dominate in winter. Further, we show that the contribution of fossil fuel combustion (eBCff) is 3.5 times greater than that of biomass burning (eBCbb). Monthly variations in mean diurnal amplitudes of eBCff and eBCbb reveal that the differences in their amplitudes (9–32%) is smallest during April–May, depicting the relative importance of biomass emissions at the diurnal scale during spring. The estimated daily radiative forcing shows that eBCff contributes more (16.4%) atmospheric forcing than eBCbb. Atmospheric forcing from both eBCff and eBCbb are higher (19.8 and 13.0 W m−2, respectively) in the afternoon than morning. These findings underscore the need for high-resolution data when researching aerosol-radiation interaction over the Himalayan area and are vital for developing aerosol mitigation plans.